Cholesterol affects retinal nerve fiber layer thickness in patients with multiple sclerosis with optic neuritis. Issue 9 (14th April 2013) - Kardys, A.; Weinstock‐Guttman, B.; Dillon, M.; Masud, M. W.; Weinstock, N.; Mahfooz, N.; Lang, J. K.; Weinstock, A.; Lincoff, N.; Zivadinov, R.; Ramanathan, M.
Abstract : Background and purpose: To evaluate the associations between retinal nerve fiber layer (RNFL) thickness and lipid profiles in multiple sclerosis (MS). Methods: This study enrolled 136 patients with MS ( n = 272 eyes; 108 females, 28 males, mean age: 46.7 ± 8.9 years); 45% had a history of optic neuritis (ON). Subjects received optical coherence tomography (OCT) testing to assess RNFL thickness and visual acuity testing with Snellen charts. A subset of 88 patients received pattern reversal visual‐evoked potential (PRVEP) testing. Lipid profiles consisting of serum high‐density lipoprotein (HDL) cholesterol, low‐density lipoprotein (LDL) cholesterol and total cholesterol (TC) levels were obtained within ± 6 months of OCT. Regression analyses were used to assess the associations between RNFL thickness and lipid profile variables. Results: Low RNFL thickness ( P = 0.008) and higher PRVEP latency ( P = 0.017) were associated with high LDL cholesterol > 100 mg/dl status. Low RNFL thickness ( P = 0.008) and higher PRVEP latency ( P = 0.043) were associated with high HDL cholesterol levels. Low RNFL thickness was also associated with HDL cholesterol > 60 mg/dl status ( P = 0.001) and with TC > 200 mg/dl status ( P = 0.015). The probability of average RNFL thickness in the lowest tertile (≤ 33rd percentile) was associated with interactions between TC > 200 mg/dl status ( P = 0.001, odds ratio = 7.5, 95% confidence interval = 2.7–21) with affected/unaffected by ON status. Conclusions: High cholesterol adversely affects RNFL thickness in patients with MS with ON.